Relationship between Parity Status and Hyperemesis Gravidarum for Pregnant Women in Tinambung District in 2020: Hubungan Status Paritas Dengan Kejadian Hiperemesis Gravidarum Ibu Hamil di Kecamatan Tinambung Tahun 2020 - Husnul Khatimah Sanusi; Darmawansyih; Nadyah; Jelita Inayah Sari (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction. Nausea and vomiting are common in early pregnancy, and they are considered to be physiologically nature. The nausea and vomiting could be severe if they continue to occur which could cause a pregnancy disorder called as hyperemesis gravidarum. The major symptom of hyperemesis gravidarum in pregnant women is the excessive nausea and vomiting. This condition could even worsen the condition of a pregnant woman in which a dehydration could occur. Based on the data from Tinambung Health Center, the numbers of pregnant women to suffer from hyperemesis gravidarum complications in Tinambung amounted to 47 women in 2018 and 58 women in 2019. From the data, it could be seen that the there was an increase of hyperemesis gravidarum cases among the community in the working area of Tinambung Health Center. Furthermore, it was also apparent that most of the pregnant women have experienced the hyperemesis gravidarum. Therefore, with the high rate of hyperemesis gravidarum cases, the researcher was interested to conduct research related to the risks of hyperemesis gravidarum on pregnant women, particularly on the mothers’ parity status.Method. The methodological approach taken in this research was analytical survey by using cross sectional study design. The sampling method used was purposive random sampling where 78 patients were selected as the samples of this study. The research was conducted through Chi-Square tests where the data was processed and analysed by using SPSS computer application program.Findings. The results of univariate test of this study indicated that the majority of respondents (46 respondents or 59.0% of total samples) were evident to experience a parity status during their pregnany. In addition, the results of the chi square test showed that the p-value = 0.000* (<0.05). Therefore, the parity status variable had been considered to have a significant influence on hyperemesis gravidarum.Conclusion. This research concluded that there are significant relationships between the parity status of pregnant women and the high cases of hyperemesis gravidarum in Tinambung disctrict.